2017
DOI: 10.1108/ijdrbe-08-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

The energy efficiency and carbon footprint of temporary homes: a case study from Japan

Abstract: Purpose The purpose of this study is to investigate the energy efficiency and life cycle carbon footprint of temporary homes in Japan after the Great Eastern Tohoku Earthquake in 2011. Design/methodology/approach An energy simulation and life cycle assessment have been done for three alternative shelter models: prefabricated shelters, wooden log shelters and sea container shelters. Findings Shelter materials have a very high share of life cycle emissions because the use period of temporary homes is short. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Regarding the effect of energy efficiency on ecological footprint or environmental degradation (CO2 emissions), some authors have studied this topic (e.g., Özbuğday et al, 2015;Kuittinen & Takano, 2017;Tajudeen et al, 2018;Ke et al, 2020;and Yao et al, 2021). However, inside this group of authors, we identified that some discovered energy efficiency decreases the ecological footprint or environmental degradation (e.g., Tajudeen et al, 2018;and Yao et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 88%
See 3 more Smart Citations
“…Regarding the effect of energy efficiency on ecological footprint or environmental degradation (CO2 emissions), some authors have studied this topic (e.g., Özbuğday et al, 2015;Kuittinen & Takano, 2017;Tajudeen et al, 2018;Ke et al, 2020;and Yao et al, 2021). However, inside this group of authors, we identified that some discovered energy efficiency decreases the ecological footprint or environmental degradation (e.g., Tajudeen et al, 2018;and Yao et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 88%
“…However, another group of authors finds that energy efficiency increases the ecological footprint or environmental degradation (CO2 emissions) (e.g., Özbuğday et al, 2015;Kuittinen & Takano, 2017;and Ke et al, 2020). Kuittinen & Takano (2017) investigated the relationship between efficiency and the carbon footprint of temporary homes in Japan in 2011.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, we chose energy production as one of the crucial factors in our research. However, as discovered by a different team of researchers, energy e ciency causes a rise in CO2 emissions, environmental deterioration, and ecological footprint (e.g., Ke et al, 2020;Kuittinen & Takano, 2017;Ozbuday et al, 2015). Kuittinen and Takano (2017) investigated the relationship between e ciency and carbon footprint in 2011 in temporary housing in Japan.…”
Section: Renewable Energy Vs Ecological Footprintmentioning
confidence: 99%